Pengembangan Modul Ajar Berbasis Karakter Untuk Program Anak Indonesia Hebat di TK Zainul Hasan - Fitriani, Rohyana; Adawiyah, Rabihatun; Ismi, Lailatul (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to develop character-based teaching modules to support the Great Indonesian Children Program at Zainul Hasan Masbagik Kindergarten. The program is designed to instil key character values such as responsibility, honesty, caring, discipline, and cooperation from an early age through a fun, contextual, and meaningful learning approach. The type of research used is Research and Development (R&D) by adapting the Borg & Gall development model, which consists of ten main steps: initial research and information gathering, planning, product draft development, initial field trial, initial product revision, main field trial, advanced product revision, operational trial, final product revision, and dissemination. The subjects in this study include teachers and group B students at Zainul Hasan Masbagik Kindergarten. Data collection techniques are carried out through observation, questionnaires, interviews, and expert validation. The data obtained was analysed qualitatively and quantitatively to determine the feasibility and effectiveness of the product. The data from the validation calculation by media experts show that the parenting module developed by the researcher can be categorized as